Energy flexible production: Saving electricity expenditures by adjusting the production plan - Rackow, Tobias; Kohl, Johannes; Canzaniello, A.; Schuderer, P.; Franke, Jörg (Procedia CIRP, 2015)
The energy turnaround in Germany increases the share of renewable energies. Since the amount of renewable energy supply is immanently subject of variation, the electricity price at the European Energy Exchange EEX is highly volatile. If companies would purchase the electricity directly at the EEX instead of from a wholesale power supplier along with price fixing, companies would benefit from increasing production in times with low electricity costs and reducing production in high-cost times. This paper shows, that influencing respectively shifting the time of electricity consumption -e.g. by adjustment of process parameter, shift period, order of jobs or machine utilization, by pausing of processes or delaying of job starts - can theoretically reduce electricity expenditures. The measures are being explained and discussed, followed by a description of company in-house and external requirements for the energy flexible production.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Energy expenditures; Energy flexibility; Energy management; Factory control; Flexible production